Accessing Unsymmetrically Linked Heterocycles through Stereoselective Palladium‐Catalyzed Domino Cyclization. Issue 1 (25th November 2021) - Arora, Ramon; Rodríguez, José F.; Whyte, Andrew; Lautens, Mark
Abstract: A palladium‐catalyzed strategy is presented to synthesize unsymmetrically linked heterocycles within stereoselective tetrasubstituted olefins. This reaction is proposed to occur via a vinyl‐Pd II intermediate capable of initiating the cyclization of various alkyne‐tethered nucleophiles. Products are formed in up to 96 % yield and excellent stereoselectivities are obtained using low catalyst loadings. This transformation was scalable up to 1 mmol and mechanistic studies suggest a syn ‐carbopalladation of the carbamoyl chloride followed by Pd II ‐catalyzed cyclization of alkyne‐tethered nucleophiles. Abstract : Solving alkynes of problems with palladium. A palladium‐catalyzed domino cyclization of alkyne‐tethered carbamoyl chlorides and aryl iodides with alkyne‐tethered aryl nucleophiles is reported. This methodology unsymmetrically links heterocycles along a tetrasubstituted olefin with >20:1 E / Z selectivity and up to 96 % yield.